Narrative of an educational path: providing a (new) meaning to medical education - Fonsêca,Graciela Soares (2019)
Abstract The need to rethink the education of health professionals, particularly doctors, is increasingly evident. This research aims at reporting the experience of a medical student of a federal institution that offers undergraduate course seats provided by the More Doctors Program. The student was encouraged to reflect upon his trajectory in the course by writing a narrative. The positive aspects indicated by him were: development of a critical attitude, knowledge integration, presence of Collective Health from the beginning of the course and use of active methodologies. Regarding the negative issues, the following was emphasized: the extensive course workload, maintenance of traditional assessments and resistance to innovation by some teachers. The student’s narrative reveals tensions, ruptures, crises and achievements that contribute to understanding the “new” medical education model and offers subsidies for its improvement.